STUDENTS’ PERCEPTION IN LEARNING SPEAKING BY VIRTUAL LEARNING ENVIRONMENT - hezy nazera; Robi Soma; Habizar (JAMBI-ENGLISH LANGUAGE TEACHING, 2022)
This study aimed to know students’ perception in learning speaking by virtual learning environment. This study employed a quantitative research with used a survey method by using questionnaires to collect the data and SPSS to analyze the data from 51 respondents from one of university in Jambi. This research expected to be useful for students and other researchers. The questionnare consist of six category in this research. The result of this research showed that in the first category got three interpretation (High, Moderate, Low) for five total item. The scale of the item rangging from 2.88 to 3.76 mean score. The second category got a moderate interpretation with the percentage 60% of the respondents chose neutral and 28% chose agree. The third and fourth category got high and moderate intepretation. The fifth and the last category got a moderate interpretation with the most of participants chose neutral. The result of the data analysis revealed that most of the students as the participants had a positive perception of learning speaking by virtual learning. Moreover the lack of internet connection should have accessible for them to get access on the internet. Beside that, 34% of the respondents prefer to learning by offline learning (traditional learning).